Performance Evaluation of Hot Mixture Asphalt Using Concentrated Rubber Latex, Rubber Compound and Synthetic Polymer as Modifier - Nyoman Suaryana; Tedi Santo Sofyan (Institute of Research and Community Outreach - Petra Christian University, 2019)
Research on the utilization of natural rubber for Hot Mixture Asphalt as modifier has been widely carried out, and more intensively since 2016 due to the declining global natural rubber price. Further research conducted is the utilization of pre-vulcanized concentrated rubber latex and rubber compound added with antioxidants and treated through vulcanization process. This study experimentally evaluates the performance of Asphalt Concrete Wearing Course (ACWC) using natural rubber and synthetic polymer as modifier, compared to ACWC without modifier (only petroleum asphalt). The results show that the rubberized asphalt has higher index penetration value as well as higher elasticity compared to petroleum asphalt penetration grade 60, but lower than synthetic polymer modified asphalt. Similarly, the level of performance of rubberized asphalt mixtures, particularly resilient modulus, water resistance, deformation, and fatigue cracking, is between that of petroleum asphalt and synthetic polymer modified asphalt